Cause of admission and mortality in geriatric patients: a hospital based study, Nepal - Acharya, Paras; Manandhar, Noora R; Acharya, Samita (Journal of Patan Academy of Health Sciences, 2017)
Introductions: As the life expectancy of people of Nepal rises, geriatric population is also on constant rise. Prevalence of diseases in this population is not well studied in Nepal. This study is carried out to assess the disease burden in geriatric in-patients and the cause of death in Patan Hospital to inform the planning process. Methods: A retrospective prevalence survey of geriatric in-patients in Internal Medicine Department in Patan Hospital was carried out using the data base record and patient's files over a period of one year. The demographics of patients, disease entity and the cause of death were recorded in Microsoft XL and were analyzed. Results: There were 1,587 patients’ charts available for analysis (out of total 1,599 admissions, 12 were excluded because charts were not found). There were 840 (52.93%) diseases of the respiratory system followed by cardio-vascular diseases 184 (11.59%) and infectious diseases 122 (7.68%). Of the 89 deaths (5.61% of 1587), 58 (65%) were due to non-communicable diseases while 31 (35%) were due to communicable diseases. The commonest cause of death was due to diseases of respiratory system 44 (COPD 20, pneumonia 18, others 6), followed by cerebrovascular accidents in 14. Conclusions: Respiratory disease was common findings in more than half of geriatric patients admitted to Patan Hospital and was also the major cause of death. Overall, non-communicable diseases accounted for two thirds of the death.